Angular streaking and sideband formation in rotating terahertz and far-infrared fields. (27th April 2017) - Kazansky, A K; Sazhina, I P; Nosik, V L; Kabachnik, N M
Abstract: Electron spectra in atomic ionization by extreme ultraviolet (XUV) or soft x-ray femtosecond pulses, in the presence of a strong circularly polarized far-infrared or terahertz (THz) field are theoretically investigated. When the XUV pulse duration is much shorter than the period of the THz field, the conditions for circular streaking are fulfilled. The peculiarities of the circular streaking are discussed. In the other extreme case when the duration of the XUV pulse is longer than the THz field period, an analog of the sidebands is formed. Special attention is paid to the intermediate case when the duration of the XUV pulse is similar to the THz period. In this case, a well-developed interference structure appears in the photoelectron spectra. A quasiclassical description of this interference structure is presented and compared with numerical calculations based on a quantum-mechanical approach.